2021
DOI: 10.1007/s00586-021-06838-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons preference for lumbar disk surgery: a discrete choice experiment

Abstract: Purpose Multiple surgical techniques are practiced to treat sciatica caused by lumbar disk herniation. It is unknown which factors surgeons find important when offering certain surgical techniques. The objective of this study is threefold: 1) determine the relative weight surgeons place on various characteristics of sciatica treatment, 2) determine the trade-offs surgeons make between these characteristics and 3) identify preference heterogeneity for sciatica treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…For instance, in general proposed advantages of minimally invasive surgery are the ability to perform the technique on an outpatient basis and the increased likelihood of a shorter recovery period, smaller scar size, and lower rate of postoperative back pain compared with open surgery, among others. 13 In this study, patients preferred hospitalization and did not necessarily seem to be influenced in their choices by the size of the scar. These results imply that a shared decision should be made by the patient and neurosurgeon based on a discussion of surgical characteristics with patients, and that not all patients would prefer minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For instance, in general proposed advantages of minimally invasive surgery are the ability to perform the technique on an outpatient basis and the increased likelihood of a shorter recovery period, smaller scar size, and lower rate of postoperative back pain compared with open surgery, among others. 13 In this study, patients preferred hospitalization and did not necessarily seem to be influenced in their choices by the size of the scar. These results imply that a shared decision should be made by the patient and neurosurgeon based on a discussion of surgical characteristics with patients, and that not all patients would prefer minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 65%
“…Aside from the lack of evidence in favor of tubular discectomy and PELD, previous research has shown that the risk of complications, the risk of recurrent disc herniation, and the effect on leg pain were the most important factors in deciding which surgical procedure is offered by surgeons. 13 Aside from the surgeons' preferences in offering certain techniques to treat sciatica, patients' own preferences might also play an important role in determining the procedure they will undergo. Currently it is unknown which characteristics of the different surgical techniques (e.g., size of the scar, ability to undergo surgery under local anesthesia) determine the preferences patients have for elective surgery for sciatica.…”
Section: Clinical Articlementioning
confidence: 99%
See 1 more Smart Citation
“…These results imply that currently perceived thresholds for acceptable surgical risk are lower than estimated by our decision model and should justifiably be shifted toward higher MELD-Na values. Risk averse behavior by clinicians and patients is not surprising, as fear of the unknown has been demonstrated to influence decision-making in other clinical scenarios . Models, such as those presented here, can help clinicians and patients to make more informed decisions.…”
Section: Discussionmentioning
confidence: 84%
“…Risk averse behavior by clinicians and patients is not surprising, as fear of the unknown has been demonstrated to influence decision-making in other clinical scenarios. [30][31][32] Models, such as those presented here, can help clinicians and patients to make more informed decisions.…”
Section: Jama Network Open | Gastroenterology and Hepatologymentioning
confidence: 99%